Safety and tolerability of ubrogepant following intermittent, high-frequency dosing: Randomized, placebo-controlled trial in healthy adults. (December 2019) - Goadsby, Peter J; Tepper, Stewart J; Watkins, Paul B; Ayele, Girma; Miceli, Rosa; Butler, Matthew; Severt, Lawrence; Finnegan, Michelle; Szegedi, Armin; Trugman, Joel M; Jakate, Abhijeet
Background: Ubrogepant is a novel, oral calcitonin gene–related peptide (CGRP) receptor antagonist in development for the acute treatment of migraine. This trial evaluated the safety and tolerability of ubrogepant, focusing on hepatic safety, when administered intermittently with high-frequency dosing to healthy participants. Methods: In this phase 1, multicenter, double-blind, parallel-group trial, healthy adults (age 18–50 years) were randomized 1:1 to placebo or ubrogepant. Ubrogepant was dosed at 100 mg (2 × 50 mg tablets) on 2 consecutive days followed by 2 consecutive days of placebo, alternating for 8 weeks. Primary outcome measures were safety and tolerability. Results: Of participants randomized (n = 518), 516 were included in the safety population (n = 260 placebo; n = 256 ubrogepant). Treatment-emergent adverse events were reported in 45% of placebo and 44% of ubrogepant participants. The most common was headache (10% placebo; 11% ubrogepant). Overall, seven cases of alanine aminotransferase and/or aspartate aminotransferase levels ≥ 3 × the upper limit of normal (five placebo, two ubrogepant) were reported and adjudicated by a panel of independent liver experts blinded to treatment. Four cases were judged unlikely related to treatment. Two cases (one placebo, one ubrogepant) were judged possibly related, and one (ubrogepant) probably related. Alanine aminotransferase increases to ≥ 3 × the upper limit of normal in the two ubrogepant cases (possibly or probably related) were transient and resolved with continued dosing; both cases were asymptomatic, with no concurrent bilirubin elevation. Conclusion: Ubrogepant was well tolerated following intermittent, high-frequency dosing in healthy participants, with no clinically relevant signal of hepatotoxicity. Trial Registration: NA.